Outcome After Decompressive Craniectomy for Middle Cerebral Artery Infarction: Timing of the Intervention. Issue 3 (15th January 2020) - Goedemans, Taco; Verbaan, Dagmar; Coert, Bert A; Kerklaan, Bertjan; van den Berg, René; Coutinho, Jonathan M; van Middelaar, Tessa; Nederkoorn, Paul J; Vandertop, W Peter; van den Munckhof, Pepijn
Abstract: BACKGROUND: Based on randomized controlled trials (RCTs), clinical guidelines for the treatment of space-occupying hemispheric infarct employ age (≤60 yr) and time elapsed since stroke onset (≤48 h) as decisive criteria whether to perform decompressive craniectomy (DC). However, only few patients in these RCTs underwent DC after 48 h. OBJECTIVE: To study the association between the timing of DC and (un)favorable outcome in patients with space-occupying middle cerebral artery (MCA) infarct undergoing DC. METHODS: We performed a single-center cohort study from 2007 to 2017. Unfavorable outcome at 1 yr was defined as a Glasgow outcome scale 1 to 3. Additionally, we systematically reviewed the literature up to November 2018, including studies reporting on the timing of DC and other predictors of outcome. We performed Firth penalized likelihood and random-effects meta-analysis with odds ratio (OR) on unfavorable outcome. RESULTS: A total of 66 patients were enrolled. A total of 26 (39%) patients achieved favorable and 40 (61%) unfavorable outcomes (13 [20%] died). DC after 48 h since stroke diagnosis did not significantly increase the risk of unfavorable outcome (OR 0.8, 95% CI 0.3-2.3). Also, in the meta-analysis, DC after 48 h of stroke onset was not associated with a higher risk of unfavorable outcome (OR 1.11; 95% CI 0.89-1.38). CONCLUSION: The outcome of DC performed after 48 h in patients with malignant MCA infarct was not worse than the outcome of DC performed within 48 h. Contrary to current guidelines, we, therefore, advocate not to set a restriction of ≤48 h on the time elapsed since stroke onset in the decision whether to perform DC.